Правова природа принципу недискримінації особистості - Калмикова, О. С. (Право, 2015)
У статті досліджено питання визначення правової природи принципу недискримінації. Висвітлено його місце і роль в системі норм міжнародного права. Робота також присвячена аналізу закріплення принципу недискримінації в міжнародних угодах і практичним питанням його реалізації. Авторка акцентувала увагу на те, що принцип недискримінації особистості є імперативною нормою jus cogens. // The article analyzes the issue of determining the legal nature of the principle of non-discrimination. His place and role in the system of norms of international law are highlighted. The work is also devoted to the analysis of fixing the principle of non-discrimination in international agreements and practical issues of its implementation. The author emphasized that the principle of non-discrimination personality is the imperative norm of Jus Cogens.
Keywords: дискримінація; права людини; ООН; заборона дискримінації; discrimination; human rights; UN; prohibition of discrimination